Evaluation and Forecast of Sustainable Utilization of Water Resources in Beijing - LI Congxin; XIANG Chunyu (Renmin Zhujiang)
Taking Beijing as the study area,this paper constructs an ecological footprint model and an ecological carrying capacity model of water resources in Beijing depending on the theory of ecological footprint of water resources.Further,it analyzes the changing trend and sustainability of water resources of the city.The grey prediction GM (1,1) model is used to predict the ecological footprint of per capita water resources in Beijing in the next three years.Reasonable suggestions are given according to the prediction results.The results indicate that the ecological footprint of water resources in Beijing shows a slow upward trend from 2000 to 2019,and the ecological footprint of water resources is much larger than the carrying capacity,which makes Beijing always in a state of ecological deficit.Moreover,the ecological pressure index of water resources is much greater than the critical value of 10,and the safety factor of water use is low.The ecological footprint of water resources of 10 000 yuan GDP presents a downward trend,indicating that the utilization rate of water resources in Beijing is increasing.The load index of water resources is quite large,which manifests that the potential for sustainable utilization of water resources is rather small and thus a large amount of water is needed to be transferred from other river basins.The forecast results show that the ecological footprint of per capita water resources in Beijing has a decreasing trend in the next three years.This is conducive to the sustainable development of water resources in Beijing and suggests that Beijing is in a good development trend.